Pattern of cognitive styles and selection of academic majors among graduates of religious and secular schools - Khairul Anwar Mastor,; Putai Jin, (Universiti Kebangsaan Malaysia, 2009)
The differences in cognitive style, school background and selection of the academic major were investigated by examining: (a) the pattern of cognitive styles among graduates from religious and secular schools, and (b) their intended selection of academic major prior to entering university. Matriculation students of Malay background (237 students from religious schools and 214 from secular schools) in selected matriculation centres in Malaysia who completed the GEFT (Group Embedded Figure Test) and a selfrated questionnaire were selected. The main result shows that there was no significant difference in cognitive styles of the respondents based on the school type. Using the contrast analyses, respondents who planned to major in Health and Technology scored higher in GEFT than those wishing to major in Arts and Law. It was also found that respondents graduated from secular schools and planned to major in Commerce were more field independent than those prospective Law major. Congruence of choice of academic major and the cognitive style orientation among respondents was then discussed.